The Influence of Personality Traits and Decision Making Style on Investment Decisions of Capital Market Investors in Bandar Lampung - Ita Fionita; Nika Renata; Satria Romanda Pratama; Diane Rahmawati; Putu Arielsi Surya Putri; Welly Widiyana Daughter (Proceeding International Conference on Information Technology and Business, 2022)
Investor behavior is one of the factors that influence stock trading transactions. Investor behavior is based on the theory of financial behavior explaining the understanding of investors' reasoning patterns in the emotional aspect and the extent to which these aspects can influence investors in the decision-making process. In previous studies personality Traits can increase the tendency of investors to seek deeper information for investment decisions, sput it out decision-making style take effect significantly and relevant to investment decisions Especially investors with a decision-making style that looks rationally and interdependently. This study aims to determine the impact of personality traits and decision-making styles on investment decisions of capital market investors in Bandar Lampung. The sampling method used in this study was non-probability sampling using a purposive sampling technique with a total of 100 respondents. Data collection methods are questionnaires or interviews and Data analysis in this study uses Multiple Linear Regression. Keywords— Personality traits, Decision making style, Financial behavior, Investment decisions (key words)